HUBUNGAN KARAKTERISTIK SOSIAL DENGAN PERILAKU KEKERASAN DALAM RUMAH TANGGA (KDRT) PADA PASANGAN SUAMI ISTRI DI KELURAHAN JATI RADEN KOTA BEKASI - Arkianti Putri (2021)
Domestic violence (KDRT) in married couples occurs because there are differences in social characteristics such as age, gender, education level, occupation, economic income, and age at marriage. This study aims to find the relationship between social characteristics and domestic violence behavior in married couples in Jati Raden Village, Bekasi City. The method used is descriptive analytic method with simple random sampling technique as many as 92 respondents. Univariate analysis used proportion test and bivariate analysis used Pearson correlation test and Spearman-rho correlation test. The results showed that there was a relationship between education level and domestic violence behavior in married couples in Jati Raden Village with a p value of 0.004 0.05, there was a relationship between income and domestic violence behavior in married couples in Jati Raden Village with a p value of 0.000 0. 0.05, and there is a relationship between married age and domestic violence behavior in married couples in Jati Raden Village with a p value of 0.000 0.05. This study provides information that domestic violence behavior can be carried out by either husband or wife, therefore the role of nurses is to overcome the psychological consequences that arise from these conditions.